Application value of bedside ultrasound for assessing volume responsiveness in patients with septic shock - He, Hao; Pan, Nifang; Zhou, Xiaoyong (Vojnosanitetski pregled, 2023)
Background/Aim. Septic shock (SS) is a complication that can occur as a consequence of an infection. As the effective circulating blood volume is of great importance in these cases, keeping constant track of the blood volume parameter is essential. The aim of this study was to explore the application value of bedside ultrasound for assessing volume responsiveness (VR) in patients with SS. Methods. A total of 102 patients with SS were selected. The volume load (VL) test was performed, and based on the results of the test, the patients were divided into two groups. The first group was the response (R) group, which had an increase in stroke volume (ΔSV) ≥ 15% after the VL test, and the second was the non-response (NR) group, with ΔSV < 15% after the VL test. There were 54 patients in the R group and 48 in the NR group. Hemodynamic parameters were compared before and after the VL test. The correlation between ΔSV and each hemodynamic index was explored by Pearson’s analysis. The receiver operating characteristic (ROC) curves were plotted for some of the parameters. Results. Before the VL test, retro-hepatic (RH) inferior vena cava (IVC) (RHIVC) distensibility (ΔRHIVC1) index, respiratory variation in RHIVC (ΔRHIVC2) index, respiratory variation in aortic (AO) blood flow peak velocity (ΔVpeakAO) index, respiratory variation in brachial artery (BA) blood flow peak velocity (ΔVpeakBA) index, and respiratory variation in common femoral artery (CFA) blood flow peak velocity (ΔVpeakCFA) index were all higher in the R group than those in the NR group (p < 0.05), while heart rate (HR), mean arterial pressure (MAP), and central venous pressure (CVP) were similar in both groups (p > 0.05). After the VL test, the R group had significantly decreased values of HR and the ΔRHIVC1, ΔRHIVC2, ΔVpeakAO, ΔVpeakBA, and ΔVpeakCFA indices, while the MAP and CVP values (p < 0.05) were increased. The NR group had a significantly decreased value of CVP (p < 0.05), while no significant changes were noticed in the values of other indices. The indices ΔRHIVC1, ΔRHIVC2, ΔVpeakAO, ΔVpeakBA, and ΔVpeakCFA significantly correlated with ΔSV (r = 0.589, r = 0.647, r = 0.697, r = 0.621, r = 0.766, respectively; p < 0.05), but there was no correlation between CVP and ΔSV (r = -0.345; p > 0.05). The areas under the curve (AUC) of ROC graphics for ΔRHIVC1, ΔRHIVC2, ΔVpeakAO, ΔVpeakBA, and ΔVpeakCFA indices, used for the prediction of VR, were 0.839, 0.858, 0.878, 0.916, and 0.921, respectively, and were significantly larger than the AUC of ROC graphic for CVP (0.691), indicating higher sensitivity and specificity of the ΔRHIVC1, ΔRHIVC2, ΔVpeakAO, ΔVpeakBA, and ΔVpeakCFA indices compared to CVP. Conclusion. Bedside ultrasound monitoring of the ΔRHIVC1, ΔRHIVC2, ΔVpeakAO, ΔVpeakBA, and ΔVpeakCFA indices can assess the VR in patients with SS more precisely.